The ecology and evolution of pangenomes - Brockhurst, MA; Harrison, E; Hall, JPJ; Richards, T; McNally, A; Maclean, C (Elsevier, 2019)
Since the first genome-scale comparisons, it has been evident that the genomes of many species are unbound by strict vertical descent: Large differences in gene content can occur among genomes belonging to the same prokaryotic species, with only a fraction of genes being universal to all genomes. These insights gave rise to the pangenome concept. The pangenome is defined as the set of all the genes present in a given species and can be subdivided into the accessory genome, present in only some of the genomes, and the core genome, present in all the genomes. Pangenomes arise due to gene gain by genomes from other species through horizontal gene transfer and differential gene loss among genomes, and have been described in both prokaryotes and eukaryotes. Our current view of pangenome variation is phenomenological and incomplete. In this review, we outline the mechanistic, ecological and evolutionary drivers of and barriers to horizontal gene transfer that are likely to structure pangenomes. We highlight the key role of conflict between the host chromosome(s) and the mobile genetic elements that mediate gene exchange. We identify shortcomings in our current models of pangenome evolution and suggest directions for future research to allow a more complete understanding of how and why pangenomes evolve.